Breeding success of the masked booby (Sula dactylatra dactylatra, Pelecaniformes:Sulidae) at Middle Cay, Pedro Bank, Jamaica - Ainsworth, Pete (2014)
The masked booby (Sula dactylatra dactylatra) colony at Middle Cay, Pedro Bank, 60 miles south of Jamaica, has been affected by challenges resulting from anthropogenic disturbances. Despite habitat degradation, the colony displays resilience by remaining extant on the cay. Between June 2008 and June 2009 we investigated the colony’s health (mainly breeding success). Data were collected once per month for twelve months and included one day, seven day and 24 hour (day and night continuous observational) sojourns. Forty-four nests were marked and monitored using a novel method for marking seabird nests based on painted seashells. Data collected from the colony included: the presence/absence/number of egg(s)/chick(s) in nests, offspring maturity, adult attendance at nests and the time of data collection. An average of 227 adult birds constituted the colony. Using the Mayfield Method and the “Naïve Estimator” for comparison, the colony’s breeding success was determined to be 37.20% despite a hatching success of 40% and a fledgling success of 93%. This is less than the estimated 45.77% success typical of healthy colonies of sulids such as the masked booby elsewhere. Based on the breeding success calculations the long term survival of this colony is at risk and needs active conservation. Rev. Biol. Trop. 62 (Suppl. 3): 159-167. Epub 2014 September 01.